TILADE AND ECONOMIC COOPERATION OF UKRAINE AND FEDERAL REPUBLIC OF GERMANY: ITS STATE, PROBLEMS AND SOLUTIONS - Flissak, Andriy (Journal of European Economy, 2018)
Officially determined on a state level the goal to economize Ukraine’s foreign economic relations foresees as necessary an all-embracing approach to combined trade, economic, and investment relationships with foreign partners. Incidentally, highest priority of our national economic policy is of real value integration into international financial and economic structures, efficient participation in international cooperation and international division of labor. Entering the European Community on the basis of equal rights remains the strategic task for Ukraine.